STRUCTURE IDENTIFICATION OF KEPAHIANG BENGKULU GEOTHERMAL FIELD USING MAGNETOTELLURIC AND GRAVITY METHODS - Ekasuci Larasati, Nindia
The Kepahiang geothermal area is tectonically located in a magmatic arc located to the west of Sumatra Island. Geothermal activity, its appearance is associated with fault structure patterns, especially those trending northeast-southwest and the main active fault zone of the Sumatran fault system trending southwest-southeast. This research was conducted to determine the depth of the caprock and reservoir and to determine the subsurface structure using magnetotelluric and gravity methods. The data is processed using Phoenix software where in the process the data is converted from the time domain to the frequency domain using the Fourier transform and processed to obtain apparent and phase resistivity. MT data is integrated with gravity. An inversion process was performed on MT using Occam's inversion for 1D and Non-Linear Conjugate Gradient (NLCG) inversion for 2D as well as the forward modeling (2D) process on gravity. Based on the results of 2D inversion and forward gravity modeling, it shows that the predicted caprock with an estimated depth of 500 – 1800 m has a resistivity value of 4 – 16 ohm.m and a density value of 2.53 gr/cc while geothermal reservoirs are located at the bottom of the caprock with an estimated depth of 1800 – 3500 m with a resistivity value of 32 – 256 Ohm-m and a density value of 2.4 gr/cc.